The feasibility and impact of deploying a four-tests panel at antenatal care in primary health care facilities of a developing country, Kenya - Missiani Ochwoto; Micah Matiang’i; Noah Machuki Onchieku; Simon Ndoria; Lydia Matoke; Maureen Otinga; Jeremiah Zablon; Evans Mathebula; Evans Mathebula; Damaris Matoke-Muhia (Frontiers in Public Health)
IntroductionContracting HIV, syphilis, hepatitis B virus (HBV), and malaria during pregnancy significantly affects the health of the woman, the pregnancy, and the unborn child. The World Health Organization (WHO) recommends testing pregnant women for these infections to achieve triple elimination of mother-to-child transmissions. However, this goal has not been fully realized in low- to medium-income countries, primarily due to segmented testing practices. This study aimed to investigate the effect of introducing a four-tests panel on the quality of antenatal care (ANC) among pregnant women attending selected Primary Health Care facilities in Kenya.MethodsUsing a multi-design approach, we analyzed ANC medical records from 577 pregnant women attending eight facilities across four different counties. Blood from the women fingerpick was tested for HIV, Syphilis Hepatitis B Virus and Malaria using the four-tests panel and the results compared to those in the medical records.ResultsOut of 577 ANC women, only 8.3% had test results for all four infections available. The majority of the mothers had been tested for syphilis (93.7%), HIV (78.5%), and malaria (62.6%), only 19.5% had been tested for HBV. Testing the women using the 4-tests panel yielded positivity rates of 6.9% for HIV, 0.9% for syphilis, 1.9% for malaria, and 1.1% for HBV. Among those without previous test results, the positivity rate was 2.8% for syphilis, 13.8% for HIV (with 10.6% testing positive for recent p24 infections, F = 24.876, p < 0.001), 2.3% for malaria, and 4.5% for HBV, with 83.3% of these individuals having no prior test results. The mean positivity rate of those tested using the 4-tests panel compared to segmented single tests was significantly different. The panel was cost-effective and user-friendly for healthcare workers, and in facilities facing staff shortages, it reduced turnaround time and workloads by half. The use of the panel also improved the profiling of ANC mothers and enhanced data management for the four infections by 91.7%.ConclusionAdopting the 4-tests panel has the potential to improve test result outputs, enhance the quality-of-service delivery, and contribute significantly to the achievement of triple elimination goals.